Redefining the role of Learning Development practitioners - Steve Briggs (Journal of Learning Development in Higher Education)
At a time when higher education (HE) sector funding is reported to be ever more perilous (Simons and Lister, 2024; Wareing, 2024) and means of making savings may need to be enacted at universities, it is essential that the unique role and impact of Learning Development (LD) practitioners is clearly understood by decision makers, for only then will it be valued and resourced. Use of non-distinct titles such as ‘third space practitioner’ or even ‘LD practitioner’, whilst interesting philosophically, hide the powerful ontological roots and epistemic practices of LD and may suggest duplication of role functions and incorrectly the potential to merge roles or teams together. In this opinion piece, I propose there is now a need to adopt greater specificity in how the role of LD practitioners is defined. I suggest this can be achieved by defining areas of activity, quantifying time spent on each and through doing so establish a taxonomy or sub-specialisms of LD practitioners. This serves to emphasise the distinctiveness of LD practitioner work and facilitates comparisons between both LD practitioners and LD community members within and between higher education institutions. It would also allow for the extent to which LD related roles are comparable to other ‘academic’, ‘non-academic’, and/or third-space roles to be determined.